Alignment-free cancelable fingerprint templates with dual protection. (March 2021) - Shahzad, Muhammad; Wang, Song; Deng, Guang; Yang, Wencheng
Highlights: New alignment-free cancelable fingerprint templates with dual protection. The proposed method has superior performance as well as heightened security. The new method outperforms almost all the existing alignment-free cancelable templates. The proposed cancelable templates are resistant to attacks via record multiplicity. The proposed cancelable templates suffer no post-transformation performance deterioration. Abstract: Cancelable biometrics is an important biometric template protection technique. However, many existing cancelable fingerprint templates suffer post-transformation performance deterioration and the attacks via record multiplicity (ARM). In this paper, we design alignment-free cancelable fingerprint templates with dual protection, which is composed of the window-shift-XOR model and the partial discrete wavelet transform. The former defuses the ARM threat and is combined with the latter to provide dual protection and enhance matching performance. The designed cancelable templates meet the requirements of non-invertibility, diversity and revocability and demonstrate superior recognition accuracy, when evaluated over public databases; for example, the Equal Error Rate of the proposed method in the lost-key scenario under the 1vs1 protocol is 0% for both FVC2002 DB1 and DB2, 1.63% for FVC2002 DB3, 7.35% for FVC2004 DB1 and 4.69% for FVC2004DB2.